EFEKTIVITAS PENGGUNAAN DANA DESA DALAM PEMBANGUNAN DESA DI KECAMATAN KARAU KUALA KABUPATEN BARITO SELATAN - Putri Nadira; Rahma Yuliani; Avela Dewi (Universitas Lambung Mangkurat, 2019)
This study aims to describe theEffectiveness of Using Village Funds on Village Development in Salat BaruVillage and Babai Village in Karau Kuala District from 2017 budget year. This research method uses a qualitative research approach with a qualitative descriptive research type. Data collection techniques used were observation, interviews, and documentation studies. Data analysis techniques are through the stages of data reduction, data presentation, and drawing conclusions/verification. The results founded that using of the Village Fund by the Salat Baru village governments or Babai village governments was still quite effective for village society when viewed from the implementation and needs of the village society because all the development programs implemented are opinions or idea from the village society. But , its can said still less effective when viewed from the implementation of the Village Minister's Regulation on the priority of using the Village Fund because in determining the goals and objectives of the use of the Village Fund only focused on physical development or village infrastructure development